Friction stir welding/processing of metals and alloys: A comprehensive review on microstructural evolution. (April 2021) - Heidarzadeh, A.; Mironov, S.; Kaibyshev, R.; Çam, G.; Simar, A.; Gerlich, A.; Khodabakhshi, F.; Mostafaei, A.; Field, D.P.; Robson, J.D.; Deschamps, A.; Withers, P.J.
Abstract: The unique combination of very large strains, high temperatures and high strain rates inherent to friction stir welding (FSW) and friction stir processing (FSP) and their dependency on the processing parameters provides an opportunity to tailor the microstructure, and hence the performance of welds and surfaces to an extent not possible with fusion processes. While a great deal of attention has previously been focused on the FSW parameters and their effect on weld quality and joint performance, here the focus is on developing a comprehensive understanding of the fundamentals of the microstructural evolution during FSW/P. Through a consideration of the mechanisms underlying the development of grain structures and textures, phases, phase transformations and precipitation, microstructural control across a very wide range of similar and dissimilar material joints is examined. In particular, when considering the joining of dissimilar metals and alloys, special attention is focused on the control and dispersion of deleterious intermetallic compounds. Similarly, we consider how FSP can be used to locally refine the microstructure as well as provide an opportunity to form metal matrix composites (MMCs) for near surface reinforcement. Finally, the current gaps in our knowledge are considered in the context of the future outlook for FSW/P.